A SOCIO-PRAGMATICS STUDY OF CONDOLENCE UTTERANCES TO THE DEATH OF BBC DISCOVERY CHANNEL, STEVE IRWIN - Nugroho, Radityo Tri; Sari, Afifah Linda (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2018)
This research is aimed at describing the intention of using condolence utterances and also determines the proper speakerâs reasons. The data are taken from virtual references called the internet. In collecting the data, the writer uses a documentary method by selecting the condolence utterances, which can be found on the internet. The first step of analyzing data is that the writer described the intention of using condolence utterances used to condole to the death of Steve Irwin. Then in determining the proper reason for using condolence, the writer used the SPEAKING theory of Hymes. Having analyzed the data, the writer finds that there are 3 intentions found in all data are to inform, to assert, and to address. And also the reason for using condolence utterances are showing intimacy, showing solidarity, showing grief, showing distress, and showing respect.